2020
DOI: 10.1016/j.jebdp.2020.101468
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Outcome Measures Used in Randomized Controlled Trials for the Treatment of Oral Lichen Planus: A Methodological Study

Abstract: This work reports on the application of a novel electric field-ionization setup for high-resolution laser spectroscopy measurements on bunched fast atomic beams in a collinear geometry. In combination with multi-step resonant excitation to Rydberg states using pulsed lasers, the field ionization technique demonstrates increased sensitivity for isotope separation and measurement of atomic parameters over previous non-resonant laser ionization methods. The setup was tested at the Collinear Resonance Ionization S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 120 publications
1
5
0
Order By: Relevance
“…Unfortunately, these interventions mostly provide the objective evidence of benefits in the majority of clinical studies and can give a misleading sense of improvement in OLP and QoL. Besides, researchers considered the different outcomes while evaluating OH-QoL in OLP in various studies [5]. Furthermore, these studies had no uniform definition for those outcomes and used different QoL tools for measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these interventions mostly provide the objective evidence of benefits in the majority of clinical studies and can give a misleading sense of improvement in OLP and QoL. Besides, researchers considered the different outcomes while evaluating OH-QoL in OLP in various studies [5]. Furthermore, these studies had no uniform definition for those outcomes and used different QoL tools for measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the current scenario in the Oral Medicine specialty, it can be advocated that the problem of heterogeneous outcome measures is confined not only to OSF but also associated with other oral diseases (Lamont et al, 2017; Taylor et al, 2017; Yan et al, 2020). The CONSORT strongly recommends the use of “completely defined pre‐specified primary and secondary outcome measures and validated scales or consensus guidelines both to enhance the quality of measurement and to assist in comparison with similar studies” (Schulz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Past literature also demonstrated a positive contribution of PRO to research and clinical practice in monitoring benefits and response to treatment (Chole & Patil, 2018;Rana et al, 2015;Rimal & Shrestha, 2015). As it is of a higher significance, added Looking at the current scenario in the Oral Medicine specialty, it can be advocated that the problem of heterogeneous outcome measures is confined not only to OSF but also associated with other oral diseases (Lamont et al, 2017;Taylor et al, 2017;Yan et al, 2020).…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Apart from psychometric strengths and operational characteristics of outcome measures, there are two additional factors requiring more attention when assessing pain intensity in the clinical trials. One is specific pain intensity domain(s) being assessed, which was found to be reported inconsistently in the literature of chronic pain and COMD including average, worst, or current pain intensity (Jensen et al., 2015; Wiriyakijja et al., 2018; Yan et al., 2020). While a patient's average pain intensity is arguably the most important outcome domain to target for pain control, a recent study comparing average and worst pain scores found that worst pain ratings were more valid and strongly associated with disabilities than other pain intensity domains (Jensen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Based upon previous comprehensive reviews, the VAS is the most frequently adopted measure of pain intensity in clinical studies (including RCTs) of COMD (Wiriyakijja et al, 2017(Wiriyakijja et al, , 2018Yan et al, 2020), followed by the NRS. The VAS possesses ratio properties, the highest level of scale measurement hierarchy, allowing for all mathematical operations and analysis on a continuum of pain intensity scores.…”
mentioning
confidence: 99%